Cystatin C improves the diagnosis and stratification of chronic kidney disease, and the estimation of glomerular filtration rate in diabetes - Rigalleau, V.; Beauvieux, M.-C.; Le Moigne, F.; Lasseur, C.; Chauveau, P.; Raffaitin, C.; Perlemoine, C.; Barthe, N.; Combe, C.; Gin, H. (Diabetes & metabolism, 2008)
Estimation of glomerular filtration rate (GFR) is recommended to diagnose and stratify chronic kidney disease (CKD). Can cystatin-C (cysC) assay improve the results in diabetic patients? In 124 diabetic patients with a wide range of GFR, as determined by 51Cr-EDTA clearance (i-GFR), we estimated ‘e-GFR’ by: the recommended Cockcroft–Gault (CG) formula and Modification of Diet in Renal Disease (MDRD) study equation; the new Mayo Clinic quadratic (MCQ) equation; the recently proposed composite estimation including both serum creatinine and cysC; and a simplified approach dividing the MDRD by cysC if less than 1.10 mg/L. The highest diagnostic accuracy (receiver operating characteristic [ROC] curves) and the highest proportions of well-stratified patients were obtained by cysC and the MDRD which, however, underestimated i-GFR for patients without CKD (−17%, P < 0.001). The CG overestimated GFR in KDOQI stages 1 and 2, ignored stage 5 and was the least accurate. The MCQ equation overrepresented stage 2, overestimating GFR at this stage (+23%, P < 0.005). The composite estimation (54.7 ± 27.0 mL per minute 1.73 m 2) correlated best with i-GFR (56.1 ± 35.3; r = 0.90, P < 0.001), and did not significantly differ from it across the entire population and within each Kidney Disease Outcome Quality Initiative (KDOQI) stage but was also biased (Bland–Altman procedure). Simply dividing the MDRD by cysC if less than 1.10 mg/L produced a comparable performance and eliminated the bias. The recommended creatinine-based estimations of GFR need to be improved. CysC assay helps in the diagnosis and stratification of CKD and leads to better estimates of GFR in diabetic patients without any substantial increase in complexity. Il est nécessaire d’avoir une estimation le débit de filtration glomérulaire (DFG) pour porter le diagnostic et préciser le stade d’une maladie rénale chronique. Le dosage de cystatine C (CysC) facilite-t-il ce travail chez les patients diabétiques ? Chez 124 patients diabétiques présentant un large éventail de DFG mesuré par clairance du 51Cr-EDTA, nous avons estimé « DFGe » par : les formules recommandées Cockcroft et Gault (CG) et Modification of Diet in Renal Disease (MDRD) ; l’équation quadratique de la Mayo Clinic (MCQ) ; une estimation composite récemment proposée et incluant à la fois la créatininémie et CysC ; une approche simplifiée en divisant simplement le résultat de MDRD par CysC si inférieur à 1,10 mg/L. Les meilleures efficacités diagnostiques (courbes ROC) et les stratifications les plus exactes ont été obtenues avec CysC et l’équation MDRD, mais cette dernière sous-estimait le DFG des patients indemnes d’atteinte rénale (−17 %, P < 0,001). La formule CG surestimait le DFG dans les stades KDOQ/I 1 et 2, ignorait le stade 5 et était la moins précise. L’équation MCQ surreprésentait le stade 2 et y surestimait le DFG (+ 23 %, P < 0,005). L’estimation composite (54,7 ± 27,0 mL par minute par 1,73 m 2) était la mieux corrélée au DFG isotopique (56,1 ± 35,3 ; r = 0,90, P < 0,001), elle n’en différait pas significativement, ni sur l’ensemble des sujets étudiés, ni dans aucun stade KDOQ/I, mais elle était biaisée (Bland & Altman). Diviser simplement le résultat de MDRD par CysC, si inférieur à 1,10 mg/L, aboutissait à des performances similaires, sans ce biais. Il faut améliorer les équations fondées sur la créatinine et recommandées pour estimer le DFG. Doser la CysC améliore le diagnostic et la stratification de l’atteinte rénale chez les patients diabétiques et contribue à mieux estimer leur fonction rénale, sans compliquer de manière importante les calculs.